Exploring Traditional Approaches for the Helping Profession: The Sufi Model - Hatta, Zulkarnain Ahmad (ASPENSI in Bandung, Indonesia, 2009)
ABSTRACT: The main aim of the helping profession such as counseling, psychology and social work is to promote well-being and quality of life. In helping alleviate human miseries that manifest in various types, these professionsâ duty is to improve human and social conditions. Meanwhile, the models of personality and psychotherapy depict spirituality in oversimplified, stereotypical terms. Sufism finds modern psychoanalytical thoughts to be agnostic. This paper is to present Sufism as a model in helping to alleviate human miseries. As the instability, contradictions, and stress of the socio-economic structure create a frantic search for relevant modes of treatment, the theories and methods espoused in Sufism can be an alternative approach to be taken up in the interest of more effective practice, especially in the field of social work, psychology and counselling. Existing measurement tools that can test the stress level will be used in order to present Sufism compatible to the mode of scientific inquiry. This paper will show that by clinging to the traditionally practices such as psychoanalytic, behavioral, transactional analysis, to name a few, would be limiting the avenues of help to those that are need. Human service workers and agencies have to work in collaboration with spiritual entities and other religious institutions in order to better serve the population.KEY WORDS: spirituality, stress, sufism, counselling, psychology, and social work.===About the Author: Dr. Zulkarnain Ahmad Hatta is a Lecturer at the School of Social Sciences, Universiti Sains Malaysia (USM), 11800 Pulau Pinang, Malaysia. He can be reached at: zulahatta@usm.edu.myHow to cite this article? Hatta, Zulkarnain Ahmad. (2009). âExploring Traditional Approaches for the Helping Profession: The Sufi Modelâ in TAWARIKH: International Journal for Historical Studies, Vol.1(1) October, pp.107-120. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (August 4, 2009); Revised (September 7, 2009); and Published (October 28, 2009).